Voltammetric determination of prifinium bromide in a pharmaceutical formulation. Issue 1 (11th December 2019) - Amro, Abdulaziz N.
Abstract : For the first time voltammetric methods have been applied and optimized for prifinium bromide (PRF) determination in pharmaceutical formulation. Cyclic voltammetry (CV) study has shown that PRF is an electroactive compound with quasi-revisable voltammograms. Optimization of voltammetric parameters indicated that platinum is the proper working electrode and (KNO3 1 M) is the proper supporting electrolyte. All applied voltammetric methods have shown high precession and accuracy. Square wave voltammetry (SWV) has shown the best limit of detection and limit of quantitation of 45.6 and 58.1 µg mL −1, respectively. Recoveries of SWV are 99.06% and 98.60% for 0.30 and 0.60 mg mL −1, respectively, using PRF tablet Riabal ® 30 mg. CV with relative standard deviation values of 0. 135 and 0.322 of intra-day repeatability and inter-day reproducibility, respectively, has the best precision.